Dwelling or Living in a Block of Flats. Towards the Polish Geography of Home - Klima, Ewa (Quaestiones Geographicae, 2013)
This article consists of two parts. The first includes a review of Polish and mainly English-language publications in geography related to the theme of home and the flat. The second part presents the results of a study of ‘homes in a block of flats’. It is primarily an attempt to identify opportunities that studying homes offers the contemporary cultural geographer. One of the aims is to pinpoint differences between the Polish and English output in this field, and to prove that such studies in our country are justified. The results clearly indicate the universal character of the notion of home and help to lift the spell of a hostile space off a block of flats. In more general categories related to the geographical understanding of space, it should be added that, as respondents indicate, this is a space which is neither homogeneous nor monotonous.